1983
DOI: 10.1056/nejm198304073081402
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition by Aspirin of Vascular and Platelet Prostaglandin Synthesis in Atherosclerotic Patients

Abstract: We studied the ability of a single oral dose of aspirin to inhibit prostacyclin synthesis by human arterial and venous tissue and to inhibit thromboxane A2 synthesis by platelets in 70 patients who were undergoing aortocoronary bypass. A dose of 40, 80, or 325 mg of aspirin was administered 12 to 16 hours before surgery. The generation of thromboxane in serum--which provides an estimate of platelet thromboxane production--was reduced from the control value by 77, 95, and 99 per cent after single doses of 40, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
2
2

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(109 citation statements)
references
References 26 publications
4
101
2
2
Order By: Relevance
“…These results indicate that a cumulative effect of very low doses of aspirin on both platelet and vascular cyclooxygenase occurs, since in the same clinical preparation a single dose of 80 mg inhibited only venous but not arterial PGI2 production (figure 4) and a single dose of 40 mg failed to inhibit either aortic or venous PG12 formation. 22 The inhibition of platelet aggregation and of thromboxane release from platelets in subjects who took 20 mg/day aspirin for a week implies that the platelets of patients with atherosclerotic coronary artery disease are not more resistant than platelets of normal subjects to the inhibitory effects of once-daily, low-dose, oral aspirin. Previous studies in normal young subjects given 20 to 40 mg of aspirin daily indicated that cumulative inhibition of TXA2 synthesis by 95% from preaspirin levels was regularly achieved after three to four such daily doses.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that a cumulative effect of very low doses of aspirin on both platelet and vascular cyclooxygenase occurs, since in the same clinical preparation a single dose of 80 mg inhibited only venous but not arterial PGI2 production (figure 4) and a single dose of 40 mg failed to inhibit either aortic or venous PG12 formation. 22 The inhibition of platelet aggregation and of thromboxane release from platelets in subjects who took 20 mg/day aspirin for a week implies that the platelets of patients with atherosclerotic coronary artery disease are not more resistant than platelets of normal subjects to the inhibitory effects of once-daily, low-dose, oral aspirin. Previous studies in normal young subjects given 20 to 40 mg of aspirin daily indicated that cumulative inhibition of TXA2 synthesis by 95% from preaspirin levels was regularly achieved after three to four such daily doses.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In this respect, studies with long-term aspirin should look not only at normal individuals but also at specific populations for whom a beneficial effect of antiplatelet therapy has been advocated (e.g., diabetics). Such individuals are significantly different from normal individuals in that they have an increased platelet turnover and decreased platelet life span,17 which may have important effects on the ability of the platelets and the vessel to recover from the effects of aspirin.…”
mentioning
confidence: 99%
“…After aspirin this value was reduced by 90% to 3.7% ± 1.5% (p<0.01). The proportion of 3 H-radioactivity present as lipoxygenase products was 21.6% ± 4.7% prior to aspirin and increased significantly (p<0.05) to 32.2% ± 8.3% after aspirin. Before aspirin 29.8% ± 8.0% of the total radioactivity released was arachidonic acid.…”
Section: Resultsmentioning
confidence: 94%